Hegemony and Slavery The Spartacus Uprising between social control and strategies of liberation - Andreas Fink (Historia.scribere)
This seminar-paper deals with slavery in the late-republican Roman Empire, in particular during the Spartacus uprising from 71 to 73 BC. It questiones how slavery as a social system could work and which mechanisms and strategies were necessary to establish this institution. To illuminate this case, the paper analyses consenting, regulative and repressing arrangements between the slaves and slave-holders. Furthermore it shows, related to the partly successful Spartacus uprising, the difficulties for the slaves to overcome the different mechanisms of hegemony.